Potential of essential oils from natural populations of Pistacia lentiscus to modify in vitro ruminal fermentation in sheep - Bettaieb A.; Attia K.; Darej C.; Moujahed N. (Innovation for sustainability in sheep and goats, 2019)
In order to evaluate the effect of Pistacia lentiscus essential oils (EOs) on in vitro rumen fermentation in sheep, leaves and twigs were collected from the Eastern Region of Tunisia (Zaghouan) in spring. The EOs were extracted by hydrodistillation and analyzed using GC/MS. Increasing doses of EOs (0 ; 5 ; 10 ; 20 ; 40 ; 80 ; 120 μL/0.5 g DM of substrate) were tested with a ration composed of ray-grass hay and concentrate (50:50 on DM basis) in inoculum according to the technique of Menke and Steingass (1988). Rumen liquor was sampled from three adult Barbarine sheep (Averaged age and body weight: 18 months and 38 kg, respectively) receiving a ration composed of 70% of oat hay and 30% of commercial concentrate. For each dose of EOs, three syringes were reserved to determine true organic matter degradability (TOMD) and two syringes were incubated for subsequent ammonia-N (NH3-N) analyses. Short chain fatty acid (SC-FA) concentration and partitioning factor (PF) were calculated. Results showed that Pistacia lentiscus EOs were composed of monoterpene Hydrocarbons (73%), associated to 16.7 % of α-pinene; 15.9% of sabinene; 12% of cis-ocimène and 11.6% of ϒ-terpinene. After 24 h of fermentation, gas production (GP) decreased (P<0.001) with the increase of EOs doses (i.e. 70.6, 82.9, 51.5 and 46.1 mL/0.5 DM, respectively for doses 20, 40, 80 and 120 μL). The same trend (P<0.0001) was observed for the estimated SC-FA concentrations. Ammonia-N concentration increased (P<0.0001) at 20 μL and reached 151.7 mg/L, and then decreased to 97.2 mg/L at 120 μL of EOs. Concerning TOMD, a trend of decrease (P < 0.0001) was noted when adding EOs and the lowest value was observed at 5 μL of EO. PF values are quite among doses 5,10 and 20 μL (averaged: 3.2), it increased significantly for 40, 80, 120 μL (4.9, 8.5, 10.9 mg/mL respectively). It was concluded that Pistacia lentiscus EOs could be envisaged as a potential additive to manipulate rumen fermentation in the optic of improving feed feeding efficiency in ruminant.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)